The word birch as a toponymic base of Polish macrotoponyms (Geographical names in physical space, 2016)
The basis of these considerations is a noun “birch”, which, due to its popularity of marked designatum, creates quite a considerable source of appelatives and toponyms. This become evident in considerable in morphological and semantic differentiation of toponyms developed based on them. The basic type is made of names that we directly derive from nouns and adjectives related with the noun “birch”, the second type comprises of names created one the toponomastic level.